A continuous spatial confining process towards high electrical conductivity of elastomer composites with a low percolation threshold. (8th February 2022) - Fu, Hongbo; Xu, Hong; Liu, Ying; Sun, Jingyao; Zhuang, Jian; Gao, Xiaolong; McNally, Tony; Wu, Daming; Huang, Yao; Wan, Chaoying
Abstract: Electrically conducting elastomer composites are indispensable in the development of flexible, wearable and soft electronic products. The continuous fabrication of highly electrically conductive polymeric composites at large scale remains a technical challenge due to the lack of control of the dispersion and orientation of the conductive fillers, interfacial interaction and filler-filler network stability in the polymer matrices. Herein, an innovative design was investigated by combining continuous compression molding and curing through a flexible roller enabled continuous process. This approach forced the alignment of short carbon fibers (SCF) along the rolling direction in a polydimethylsiloxane (PDMS) matrix due to the deformation of the flexible roller and effectively condensed the conductive SCF network in PDMS. The distance between SCFs can be further reduced with the rolling cycles which is ascribed to a spatial confining-forced network assembly. With a rolling cycle of 20, dual electrical conducting percolation thresholds reached at 0.1 wt% and 0.5 wt% SCF, respectively. A maximum electrical conductivity of 49.69 S/m was achieved with a SCF loading of 4 wt%. A fiber contact model was proposed to predict the electrical conductivity of the composites. The PDMS/SCF composites were tested for conductive electrodes and flexible pressure sensors. The present work provides a facile method for continuous fabrication of conductive elastomeric composites, with potential for continuous fabrication of thermosetting composites. Graphical abstract: Image 1